High resolution temperature and density profiles during the energy quench of density limit disruptions in Rijnhuizen tokamak project - F. Salzedas (2002)
Measurements of the electron temperature, Te, and density, ne, during the energy quench of a major disruption showed that the onset of Te erosion in the neighborhood of the m/n = 2/1 O point at the low field side (LFS) accelerates the well-known m/n = 1/1 erosion of the core temperature. During this phase Te(r) is only partially flat in the region between the q = 2 and the q = 1 surfaces and ne(r) decreases in the core and increases inside the m/n = 2/1 island. Immediately after the flattening of Te(r) a large peak in Te and to a lesser extent in ne has been observed. This peak is radially localized at the q = 2 radius at the LFS, is very short lived and is poloidally asymmetric. Te profiles measured by the heterodyne radiometer and the Thomson scattering agree very well up to the time Te(r) flattens but afterwards can be a factor of two different.